2008
DOI: 10.1016/j.exer.2008.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extracellular matrix and neighboring cells on induction of human embryonic stem cells into retinal or retinal pigment epithelial progenitors

Abstract: To determine the effects of extracellular matrix and neighboring cells on the differentiation of human embryonic stem cells (hESC) into progenitors of retinal cells and/or retinal pigment epithelium (RPE). HESC were cultured on mouse PA6 stromal cells for approximately 2 weeks to obtain neural progenitors. To induce photoreceptor marker expression, the neural progenitors were cultured on a confluent monolayer of ARPE19 or on laminin-coated dishes. To induce RPE markers, the neural progenitors were seeded onto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 48 publications
1
53
0
2
Order By: Relevance
“…In some cases, very complex culture strategies have been used, including the sequential addition and withdrawal of factors and purification of specific cell populations during the culture period (Fang et al, 2006;Wang et al, 2005). As for the induction of ocular tissues, lens and several retinal cell types were reported to have been differentiated from ES cells (Gong et al, 2008;Lamba et al, 2006;Osakada et al, 2008). Factors regulating the differentiation of the retinal tissues, such as Wnt2b, Wnt3a, Notch, Hes1, and RA (Jadhav et al, 2006;Kubo et al, 2003;Luo et al, 2006;Osakada et al, 2007;Tomita et al, 1996), were sequentially added to induce specific retinal cell lineages such as photoreceptor cells (Osakada et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, very complex culture strategies have been used, including the sequential addition and withdrawal of factors and purification of specific cell populations during the culture period (Fang et al, 2006;Wang et al, 2005). As for the induction of ocular tissues, lens and several retinal cell types were reported to have been differentiated from ES cells (Gong et al, 2008;Lamba et al, 2006;Osakada et al, 2008). Factors regulating the differentiation of the retinal tissues, such as Wnt2b, Wnt3a, Notch, Hes1, and RA (Jadhav et al, 2006;Kubo et al, 2003;Luo et al, 2006;Osakada et al, 2007;Tomita et al, 1996), were sequentially added to induce specific retinal cell lineages such as photoreceptor cells (Osakada et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It has been established that cells exposed to a target ECM will more easily differentiate toward the target tissue, 31,32 where one of the reasons for this ECM-specific differentiation may be because native ECM may have the potential to retain the growth factors that will steer the differentiation toward the specific target tissue. 4 Decellularizing cartilage ECM may not only alter the matrix architecture but it may also furthermore remove some of these important growth factors, affecting the bioactivity of the cartilage ECM.…”
mentioning
confidence: 99%
“…In other studies, co-culture of human retinal neurospheres with RPE prolonged and enhanced the growth of human prenatal retinal neurospheres, which went on to express numerous neurodevelopmental and eye specification genes and markers characteristic of neural and retinal progenitor cells (Gamm et al, 2008). Gong et al cultured hESC-derived neural progenitors on the ARPE19 RPE cell line and also observed expression of the photoreceptor precursor markers Crx and Nrl (Gong et al, 2008). However, they never attempted to obtain 3D tissue constructs.…”
Section: Importance Of Rpe Co-culturementioning
confidence: 99%